Comprehensive NMR analysis of two kinds of post-fermented tea and their anti-glycation activities in vitro. (30th March 2019) - Zhang, Mimin; Otake, Kenichiro; Miyauchi, Yumiko; Yagi, Masayuki; Yonei, Yoshikazu; Miyakawa, Takuya; Tanokura, Masaru
Highlights: NMR is used to characterize the compositional changes of two different dark teas. Catechin metabolisms are different between aerobic and anaerobic fermentations. Anaerobic fermentation using LAB retains anti-glycation activity of dark tea. Pyrogallol is a potent anti-glycation metabolite produced in the LAB fermentation. Abstract: Post-fermented tea (dark tea) is produced from enzyme-inactivated fresh tea leaves by microbial fermentation. Batabata tea and Awaban tea are two major dark teas fermented under aerobic and anaerobic conditions, respectively. However, how their chemical compositions and functionalities change during different post-fermentation processes remains unclear. Nuclear magnetic resonance (NMR)-based analyses showed that (−)-epigallocatechin gallate (EGCG), (−)-epigallocatechin (EGC) and (−)-epicatechin (EC) decreased in Batabata tea during post-fermentation with aerobic molds. In contrast, EGC and EC increased, and pyrogallol was produced in Awaban tea during post-fermentation with lactic acid bacteria (LAB). The anti-glycation activities of two dark teas were investigated using an in vitro assay system with human serum albumin (HSA). The anti-glycation activity decreased in Batabata tea, but it was retained in Awaban tea during post-fermentation. Our results showed that post-fermentation with LAB was an efficient way to enhance phenol content and that pyrogallol contributed to anti-glycation activity of Awaban tea.